Peroxisome proliferator‐activated receptor‐γ activation inhibits hepatocellular carcinoma cell invasion by upregulating plasminogen activator inhibitor‐1 - Pang, Xiaojuan (Cancer Sci, 2013)
The peroxisome proliferator‐activated receptor‐γ (PPARγ) is a ligand‐activated transcription factor belonging to the nuclear receptor superfamily. Peroxisome proliferator‐activated receptor‐γ ligands can inhibit cell growth and increase apoptosis of cancer cell lines, suggesting a potential role for PPARγ as a tumor suppressor. Whereas the related studies between PPARγ and cancer cell invasion are still poor. Our previous study indicates that β‐estradiol (E2) suppresses hepatocellular carcinoma (HCC) cell invasion. We report here that E2 can activate PPARγ of HCC cells, and activated PPARγ suppresses cell invasion by upregulating the expression level of plasminogen activator inhibitor‐1 (PAI‐1). We found that PPARγ plays an important role in the E2‐induced HCC cell invasion process. Using PPARγ agonist GW1929, a reduced invasion effect was found in HCC cell lines, and this inhibition of cell invasion was dosage‐dependent. However, cell invasion was restored by treatment with PPARγ antagonist GW9662. The activated PPARγ upregulated the expression of cell migration‐related protein PAI‐1. Furthermore, knockdown of PPARγ in HCC cells decreased the level of PAI‐1 and advanced cell invasion in response to GW1929. On the contrary, overexpression of PPARγ in HCC cells elevated the level of PAI‐1 and inhibited cell invasion. These findings suggest that PPARγ activation inhibits HCC cell invasion via the upregulation of PAI‐1 and implicate that PPARγ is a target for the treatment and prevention of HCC cell invasion.